2012
DOI: 10.1063/1.4707006
|View full text |Cite
|
Sign up to set email alerts
|

Cryostat design and development for a superconducting undulator for the APS

Abstract: The Advanced Photon Source (APS) upgrade project at Argonne National Laboratory includes the implementation of superconducting undulator insertion devices. A development program is under way to build, test, and operate a prototype device in the storage ring. We present the overall design concept including superconducting magnet structure, cryocooler-based cooling system, and cryostat as well as a status report on the R&D program. Results of cryocooler performance characterization using a model magnet in a test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The original concept and main engineering solutions for the first APS SCU cryostat came from the experienced team of SC wigglers designers/builders at Budker Institute of Nuclear Physics in Novosibirsk, Russia [22]. The cryogenic system [142] of this cryostat (see Fig. 14) consists of three thermal circuits, each operating at its nominal temperature of approximately 4, 20, and 60 K.…”
Section: Cryogenic and Vacuum Systemmentioning
confidence: 99%
“…The original concept and main engineering solutions for the first APS SCU cryostat came from the experienced team of SC wigglers designers/builders at Budker Institute of Nuclear Physics in Novosibirsk, Russia [22]. The cryogenic system [142] of this cryostat (see Fig. 14) consists of three thermal circuits, each operating at its nominal temperature of approximately 4, 20, and 60 K.…”
Section: Cryogenic and Vacuum Systemmentioning
confidence: 99%
“…Below we present the main conceptual points of the SCU1 design. A more detailed description can be found in [12][13][14].…”
Section: Design Of Scu1mentioning
confidence: 99%
“…The SCU1 uses a cryostat that is an improved version of the SCU0 cryostat [13]. Modifications include the addition of optical windows in the cryostat vacuum vessel that allow direct observation and measurement of the cold mass vertical position inside the cryostat.…”
Section: B Cryostatmentioning
confidence: 99%
“…Test results indicated that helium circulation via the predominantly horizontal thermosiphon could be enhanced with an additional heater mounted on a vertical helium return pipe [12]. Provision for such a heater has been implemented in the SCU cryostat design [11].…”
Section: B Cryostat and Cooling Systemmentioning
confidence: 98%